Mood Variation of Clauses on Jokowi’s Speech - Adi Manggala Saputro; Duwi Handayani; Malikatul Laila (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The aims of this study are:(1) to identify the intention of Jokowi’s expression during his speech in front of audiences from various representative states and (2) to describe Jokowi’s utterances seen from mood variation in the perspective of SFL. This study is in the domain of descriptive and qualitative. The primary data are taken from Youtube about Jokowi’s speech at APEC ON PEC CEO SUMMIT 2014. The secondary data covers the social backgrounds and personality of Jokowi. The data analysis is carried out by applying SFL theory of Pragmatics and Discourse. The result of this study shows that the function of Jokowi’s expression is systematized as in mood variation. From the data of clauses showing expressive utterance, it can be explained that the characteristics of Jokowi’s utterances reflect his personality based on the context of utterances. Moreover, based on mood variation, the use of finite can be seen from Auxillary, pronoun, and modality. These components explain Jokowi’s joys and thanks to the audience.